The DAL81 gene product is required for induced expression of two differently regulated nitrogen catabolic genes in Saccharomyces cerevisiae. - Bricmont, P A (1991)
We demonstrate that the DAL81 gene, previously thought to be specifically required for induced expression of the allantoin pathway genes in Saccharomyces cerevisiae, functions in a more global manner. The data presented show it to be required for utilization of 4-aminobutyrate as a nitrogen source and for 4-aminobutyrate-induced increases in the steady-state levels of UGA1 mRNA. The DAL81 gene encodes a 970-amino-acid protein containing sequences homologous to the Zn(II)2Cys6 motif and two stretches of polyglutamine residues. Deletion of sequences homologous to the Zn(II)2Cys6 motif did not result in a detectable loss of function. On the other hand, loss of one of the polyglutamine stretches, but not the other, resulted in a 50% loss of DAL81 function.